Ekshibitionistiske selvudslettelser. Autoreception og genskrivning hos Jørgen Leth og clausbeck-nielsen.net - Iversen, Stefan (Passage - Tidsskrift for litteratur og kritik, 2010)
Stefan Iversen: “Exhibitionistic Erasures of the Self: Autoreception and Re-writing in Works by Jørgen Leth and clausbeck-nielsen.net” Taking its point of departure in the observation that recent Scandinavian literature and art have seen an increase in the number of works dealing with transgressions of the divide between the work of art as an autonomous entity and the artist as a concrete individual, this article sets out to investigate what it terms ‘autoreception’ and ‘rewriting’ in two already canonical works by Jørgen Leth and clausbeck-nielsen.net. The main argument is that not only are these two works composed by using a rewriting strategy, they also draw a lot of their highly original aesthetic and ethic impetus from it.